Roles of Atomic Injection Rate and External Magnetic Field on Optical Properties of Elliptical Polarized Probe Light. (1st January 2016) - Karimi, R.; Asadpour, S.H.; Batebi, S.; Soleimani, H. Rahimpour
Abstract: In this paper we investigate the optical properties of an open four-level tripod atomic system driven by an elliptically polarized probe field in the presence of the external magnetic field and compare its properties with the corresponding closed system. Our result reveals that absorption, dispersion and group velocity of probe field can be manipulated by adjusting the phase difference between the two circularly polarized components of a single coherent field, magnetic field and cavity parameters i.e. the atomic exit rate from cavity and atomic injection rates. We show that the system can exhibit multiple electromagnetically induced transparency windows in the presence of the external magnetic field. The numerical result shows that the probe field in the open system can be amplified by appropriate choice of cavity parameters, while in the closed system with introduce appropriate phase difference between fields the probe field can be enhanced. Also it is shown that the group velocity of light pulse can be controlled by external magnetic field, relative phase of applied fields and cavity parameters. By changing the parameters the group velocity of light pulse changes from subluminal to superluminal light propagation and vice versa.